Quercetin Ameliorates Renal Injury and Pyroptosis in Lupus Nephritis through Inhibiting IL-33/ST2 Pathway In Vitro and In Vivo - Hsin-Yuan Chen; Yi-Fen Chiang; Yong-Han Hong; Tzong-Ming Shieh; Tsui-Chin Huang; Mohamed Ali; Hsin-Yi Chang; Kai-Lee Wang; Shih-Min Hsia (MDPI AG, 2022)
Lupus nephritis (LN) is a common and serious symptom in patients with systemic lupus erythematosus (SLE). Tubular interstitial fibrosis is a common underlying mechanism in the development of lupus nephritis to end-stage renal failure (ESRD). Quercetin is widely proven to prevent tissue fibrosis. Therefore, the purpose of this study is to investigate the beneficial effects of quercetin on the inhibition of fibrosis and inflammation pathways in in vitro and in vivo lupus nephritis models. In the current study, MRL/lpr mice as animal models, and HK-2 human renal tubular epithelial cells were stimulated by interleukin-33 (IL-33) to mimic the cellular model of lupus nephritis. Immunohistochemical staining, immunoblotting assay, immunofluorescence staining, and quantitative real-time polymerase chain reaction assay were used. The in vivo results showed that quercetin improved the renal function and inhibited both fibrosis- and inflammation-related markers in MRL/lpr mice animal models. The in vitro results indicated that quercetin ameliorated the accumulation of fibrosis- and inflammation-related proteins in IL-33-induced HK-2 cells and improved renal cell pyroptosis via the IL33/ST2 pathway. Overall, quercetin can improve LN-related renal fibrosis and inflammation, which may offer an effective potential therapeutic strategy for lupus nephritis.